The Influence of Digital Transformation and Information Management on the Efficiency of Hospital Services - Bayhaqi, Muhamad; Asri, Asri; Syahrir, Irwan; Wiliyanarti, Pipit Festi (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Digital transformation in the health sector aims to improve the quality and efficiency of services. However, the implementation of SIMRS, RME, and SATUSEHAT still faces various obstacles, such as infrastructure limitations, low digital literacy among health workers, and data security issues. Evaluating the effectiveness of digitization and the factors that influence it is important.Objective: This study aims to analyze the influence of digital transformation and information management on the efficiency of healthcare services at Hospital B.Methods: This study uses a quantitative correlational approach with a Likert scale questionnaire. A total of 57 respondents from healthcare workers and management were selected using purposive sampling. Data were analyzed using multiple linear regression after undergoing validity, reliability, and classical assumption tests.Results: The majority of respondents were female (63%), had more than 10 years of work experience (58%), and held functional positions (62%). Digital transformation did not significantly affect service efficiency (p = 0.432), while information management had a significant effect (p = 0.012). Both variables explained 19.8% of the variation in service efficiency (R² = 0.198).Conclusion: Hospitals are advised to prioritize strengthening information management through enhancing human resource capacity, integrating information systems, and developing digital infrastructure. Further research is recommended to explore other variables such as organizational culture and digital leadership